The compatibility of the film adaptations and tragic versions of the egyptian queen cleopatra as a woman with the belief and management system that fed cleopatra - ALGÜL, NEVİN (My University, 2022)
The compatibility of the film adaptations and tragic versions of the Egyptian Queen Cleopatra as a woman with the belief and management system that fed Cleopatra. Although the perception of women in comparatively accepted religions and belief systems is the subject of another research with its wide scope, in this study, which will only be used as a tool to determine the opposite and sharpen its lines; The main aim is to try to measure how close the written and visual products created about Cleopatra can be with her possible reality. It will be one of the priority issues to examine the female queen identity of the period through the perception of gender.
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC); Cleopatra; Egypt; Woman; Gender; Osiris; Isis; Horus; Cinema; Tragedy